German Labor Market and Fiscal Reforms 1999 to 2008: Can They be Blamed for Intra-Euro Area Imbalances? - Niklas Gadatsch; Nikolai Stähler; Benjamin Weigert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we assess the impact of major German structural reforms from 1999 to 2008 on key macroeconomic variables within a two-country monetary union DSGE model. By many, these reforms, especially the Hartz reforms on the labor market, are considered to be the root of thereafter observed imbalances in the Euro Area. We find that, in terms of German GDP, consumption, investment and (un)employment, the reforms were a clear success albeit the impact on the German current account was only minor. Most importantly, the rest of the Euro Area benefited from positive spillover effects. Hence, our analysis suggests that the reforms cannot be held responsible for the currently observed macroeconomic imbalances within the Euro Area.
Keywords: E62; E32; H20; 330